# Difference between revisions of "1962 AHSME Problems/Problem 3"

(→Problem) |
(→Solution) |
||

Line 6: | Line 6: | ||

==Solution== | ==Solution== | ||

− | + | Let <math>y</math> represent the common difference between the terms. We have <math>(x+1)-y=(x-1)\implies y=2</math>. | |

+ | |||

+ | Substituting gives us <math>(2x+3)-2=(x+1)\implies 2x+1=x+1\implies x=0</math>. | ||

+ | |||

+ | Therefore, our answer is $\textbf{(B)}\ 0\qquad$ |

## Revision as of 23:06, 9 November 2013

## Problem

The first three terms of an arithmetic progression are , in the order shown. The value of is:

## Solution

Let represent the common difference between the terms. We have .

Substituting gives us .

Therefore, our answer is $\textbf{(B)}\ 0\qquad$